911: What's Your Emergency? - Roche, Hannah (The Meducator, 2016)
Emergency medicine is a central branch of medicine focusing on the immediate decisions and action necessary to prevent death or disability. I have had the opportunity to observe the inner workings of the emergency medical systems both locally here in Hamilton, and globally. The stark contrast in emergency healthcare between developed and developing nations raises distinct observations regarding measures that need to be taken to address the dire need of certain situations. While in Canada we wait mere hours in sanitary emergency rooms, millions – even billions – of people around the globe may wait days, months or beyond to be seen or treated. This inevitably leads to a drastically increased, and regrettably avoidable, mortality rate. Yet the issue is not typically an isolated one. Issues of greater importance like this, in the context of a developing nation, are often rooted and symptomatic of ongoing struggles of poverty, corruption, and violence. This perspective aims to compare and contrast emergency medical systems across global platforms in an effort to bring to light the immediate need for drastic intervention. Moreover, this intervention must stem from within a national infrastructure, resulting in a concerted effort to target this devastating cycle of poverty, disease, and death.